A Porous and Conductive Graphite Nanonetwork Forming on the Surface of KCu7S4 for Energy Storage - Shen, Wei-Xia; Xu, Jun-Min; Dai, Shu-Ge; Zhang, Zhuang-Fei (Frontiers in Chemistry, 2018)
A flexible all-solid-state supercapacitor is fabricated by building a layer of porous and conductive nanonetwork on the surface of KCu7S4 nanowires supported on the carbon fibre fabric, where the porous and conductive nanonetwork is assembled by graphite nanoparticles. This porous graphite layer plays a key role in providing ion diffusion channels to access the KCu7S4 through the pores for electrochemical reactions and forming electron transport pathways from the graphite network to the electronic collector of the carbon fiber fabric. This flexible supercapacitor exhibits excellent electrochemical performance with high specific capacitance of 408 F g-1 at a current density of 0.5 A g-1 and high energy density of 36 Wh kg-1 at a power density of 201 W kg-1. Moreover, it is cost-effective, easy to scale up and environmentally friendly with high flexibility. Our investigation demonstrates that such a porous and conductive nanonetwork could be used to improve the charge storage efficiency for a wide range of electrode materials.